Strength Analysis of SUS304 and SUS440 Stainless Steel Materials for Piping in DI Water Systems - Nanta W.K.P; Muhammad Lyan Syaputra; Dimas Abdul Rabian (METALOGRAM, 2025)
This study presents a strength analysis of SUS304 and SUS440 stainless steel materials in the context of their suitability for piping applications in Deionized (DI) water systems. Stainless steel materials, particularly SUS304 (austenitic) and SUS440 (martensitic), are often considered for piping systems due to their durability, corrosion resistance, and mechanical properties. The objective of this research is to evaluate and compare the tensile strength, corrosion resistance, and long-term performance of these two materials when exposed to the specific conditions of DI water environments. SUS304 is known for its excellent resistance to corrosion, making it a widely used material for pipes and fittings in systems that transport water, food, and beverages. Its superior formability, high ductility, and resistance to oxidation at ambient temperatures have made it a popular choice for water distribution systems. In contrast, SUS440 offers higher hardness and wear resistance, which is particularly advantageous for components subjected to high mechanical stress. However, its corrosion resistance is generally inferior to that of SUS304, particularly in environments exposed to chlorides and other corrosive agents commonly found in DI water. The strength analysis in this study involved testing the materials for tensile strength, hardness, and resistance to corrosion under simulated DI water conditions. Both materials underwent mechanical testing, including tensile testing, microhardness testing, and accelerated corrosion testing. The results show that SUS304 demonstrated superior corrosion resistance, making it more suitable for DI water systems, where prolonged exposure to moisture and trace chemicals could lead to degradation. SUS440, while showing higher tensile strength and hardness, exhibited lower corrosion resistance, which could lead to material failure over time when exposed to DI water. This study concludes that SUS304 is the more appropriate material for piping in DI water applications due to its superior corrosion resistance and adequate mechanical strength for typical water transport systems. However, SUS440 may be considered for specific components requiring higher wear resistance but with additional measures to address potential corrosion issues.